Customer Satisfaction: Rantasipi Ikaalinen Spa - Borodulin, Henna (Tampereen ammattikorkeakoulu, 2013)
The aim of this study is to provide information about the customer satisfaction level in Rantasipi Ikaalinen spa and to collect ideas for potential products which could generate added value to the already existing services. The study is quantitative and the empiric part was conducted as a questionnaire survey in the spa in February and March of 2013. Spa tourism and especially wellness tourism is a rising phenomenon around the globe now when many work environments become increasingly stressful and hectic. People look for a place to refresh their mind and body. To be the first to respond to the changing needs of the customers, a good knowledge of the existing customer satisfaction level is required. A firm understanding of customers enables improving the company and its services. The customer satisfaction in Ikaalinen spa is on a very good level. Many respondents experienced the services in the spa positively and would visit Ikaalinen spa again. The questions about potential products received a few ideas for improvement. Future customer satisfaction study should be carried out in Ikaalinen spa, as it has been through many forums. The marketing of the different wellness services in the spa should receive more marketing attention because of the perceived usage percentage among the respondents.